Barriers in obtaining primary health care services from public clinics by non-citizen labors in Malaysia - Sohrabi, M.; Osman, Ahmad Farid; Tumin, M. (Asia Pacific Higher Learning Sdn Bhd., 2018)
Non-citizen labors in the country have been found to face difficulties in accessing healthcare services. The study seeks to investigate the existence of barriers in accessing primary healthcare services by non-citizen labors in Malaysia. This study was conducted on 323 non-citizen labors residing in the urban areas of Malaysia, particularly of Johor Bahru and Klang Valley from May to September 2017. Relevant information regarding the personal barriers (language, preference for physician’s gender, difficulty taking leave from work), structural barriers (availability of public clinic in residential area, travel time to the public clinic, physician’s knowledge and skill) and financial barriers (insurance coverage, fear of losing daily income, transportation costs) on using primary healthcare services at public clinics were obtained. The result of the analysis revealed that the barriers cited by non-citizens to seek primary healthcare in Malaysia were lack of medical insurance protection (75.1%), non-availability of a public clinic in the residential area (38.7%), not receiving the needed or wanted services (21.3%), long travel time to the nearest public clinic (17.3%), language (10.2% of respondents), negative perception about the doctors’ knowledge and skills (9.9%), difficulty taking leave (7.8%), fear of losing daily income (7.7%), high transportation cost (3.7%) and different doctor gender preference (2.5%). Therefore, barriers to access healthcare services among non-citizens exist in Malaysia.